Association between bacterial homoplastic variants and radiological pathology in tuberculosis - Grandjean, Louis; Monteserin, Joha; Gilman, Robert; Pauschardt, Julia; Rokadiya, Sakib; Bonilla, Cesar; Ritacco, Viviana; Vidal, Julia Rios; Parkhill, Julian; Peacock, Sharon; Moore, David AJ; Balloux, Francois (Thorax, 2020)
BackgroundUnderstanding how pathogen genetic factors contribute to pathology in TB could enable tailored treatments to the most pathogenic and infectious strains. New strategies are needed to control drug-resistant TB, which requires longer and costlier treatment. We hypothesised that the severity of radiological pathology on the chest radiograph in TB disease was associated with variants arising independently, multiple times (homoplasies) in the Mycobacterium tuberculosis genome.MethodsWe performed whole genome sequencing (Illumina HiSeq2000 platform) on M. tuberculosis isolates from 103 patients with drug-resistant TB in Lima between 2010 and 2013. Variables including age, sex, HIV status, previous TB disease and the percentage of lung involvement on the pretreatment chest radiograph were collected from health posts of the national TB programme. Genomic variants were identified using standard pipelines.ResultsTwo mutations were significantly associated with more widespread radiological pathology in a multivariable regression model controlling for confounding variables (Rv2828c.141, RR 1.3, 95% CI 1.21 to 1.39, p<0.01; rpoC.1040 95% CI 1.77 to 2.16, RR 1.9, p<0.01). The rpoB.450 mutation was associated with less extensive radiological pathology (RR 0.81, 95% CI 0.69 to 0.94, p=0.03), suggestive of a bacterial fitness cost for this mutation in vivo. Patients with a previous episode of TB disease and those between 10 and 30 years of age also had significantly increased radiological pathology.ConclusionsThis study is the first to compare the M. tuberculosis genome to radiological pathology on the chest radiograph. We identified two variants significantly positively associated with more widespread radiological pathology and one with reduced pathology. Prospective studies are warranted to determine whether mutations associated with increased pathology also predict the spread of drug-resistant TB.